2000
DOI: 10.1007/s002280000142
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hospitalisation on liver enzymes in healthy subjects

Abstract: Hospitalisation, although it is believed to protect subjects from confounding environmental factors, can itself be associated with increases in liver enzyme levels. The definition of a relevant increase can be used to identify subjects who need further evaluation. The cause of the increase in liver enzyme levels remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 12 publications
1
24
0
1
Order By: Relevance
“…Furthermore, three subjects had elevated alanine aminotransferase levels at screening. Indeed, these elevations may have been the result of the subjects being confined within the trial unit for a prolonged period, an effect that has been observed in placebo recipients in numerous Phase I clinical studies [31, 32]. Similar transient elevations have been observed in other Phase I studies with rivaroxaban [19].…”
Section: Discussionmentioning
confidence: 66%
“…Furthermore, three subjects had elevated alanine aminotransferase levels at screening. Indeed, these elevations may have been the result of the subjects being confined within the trial unit for a prolonged period, an effect that has been observed in placebo recipients in numerous Phase I clinical studies [31, 32]. Similar transient elevations have been observed in other Phase I studies with rivaroxaban [19].…”
Section: Discussionmentioning
confidence: 66%
“…Terbogrel was well tolerated and had only minor effects on haemostasis. Liver enzymes were found to be elevated in a small number of subjects in all treatment groups, which may be due to the lack of exercise during their stay in the Human Pharmacological Center [18]. The therapeutic potential of a combined TxA 2 receptor/synthase inhibitor may substantially exceed that obtained by blocking TxA 2 alone.…”
Section: Discussionmentioning
confidence: 94%
“…Studies of ambulatory subjects have consistently reported that the highest observed elevation is less than 3 times the upper limit of normal [3-5,18], while studies of subjects confined to a clinical research facility reported elevations more than 8 times the upper limit of normal [2,6]. While the exact reason for these differences is not clear, there is meta-analytic evidence that subjects on a clinical research unit may increase their aminotransferase activity independent of treatment [19]. This meta-analysis compared the change in ALT for the placebo groups in studies where subjects were admitted to a clinical research unit to the change in ALT for the placebo group in studies where subjects were ambulatory.…”
Section: Discussionmentioning
confidence: 99%